An integrated prediction model for the dynamics of machine tool spindles. Issue 6 (2nd November 2018) - Feng, Wei; Liu, Baoguo; Yao, Bin; Cui, Zhongming; He, Qingshan; Wang, Xing
ABSTRACT: The predictility of dynamics of the machine tool spindles is essential for machining precision. During machining, the machine tool components and the cutting process interact with each other. Accordingly, it is necessary to take the process-machine interaction effects into account in order to predict the spindle's dynamics accurately. This paper presents an integrated model for the prediction of a spindle's dynamics. The model synthesizes the interactive influence between machine dynamics and forces in grinding process. The thermo-mechanical model of the spindle with angular contact ball bearings was built by using the finite-element method. The analytical model was used to calculate the process forces. A coupled simulation was adopted to accomplish the interactive process between the two models. Basing on the integrated model, the bearing stiffness, the natrual frequency, the spindle tip stiffness and deformations of a grinder's spindle were investigated. The prediction of the deformation fluctuations at the spindle tip due to process-machine interaction was also achieved.